Unmanned Aerial Vehicles (UAVs) for vegetation index analysis in traditional agriculture - Calvache-Muñoz, David Andres; Benavides-Cardona, Carlos Andrés; García, Javier (Revista de Ciencias Agrícolas, 2025)
The use of spectral remote sensing in agriculture allows the obtaining of relevant and accurate data on crop vigor in in a short time. This makes it possible to make decisions that improve farmers' profitability. This study defines the use of remote sensing devices that capture electromagnetic regions represented in multispectral images from the visible red (RED) and near-infrared (NIR) bands to evaluate the spectral response in a potato crop. The images obtained allowed the calculation of the Normalized Difference Vegetation Index (NDVI) and the Soil-Adjusted Vegetation Index (SAVI) to compare spectral responses in different phenological stages of a potato crop. These results were verified in the field to establish the causes of the negative and positive values in the calculation of the indices. In the early stages of crop development, there were areas with NDVI and SAVI values (-0.3 and -0.4) corresponding to the reflectance in bare soil. In later stages, such as flowering and filling, there were positive values of NDVI and SAVI (0.06 and 0.1) in most of the areas studied; negative values (-0.2 and -0.4) were also found, indicating problems of vegetative development associated with the presence of invasive plant species, highlighting the correction of reflectance between the two indices. The results obtained show that the vegetation indices allow the identification of characteristics and conditions in the potato crop, thus demonstrating the technical feasibility of this technological tool in production systems in the region.